Influences of genetically predicted and attained education on geographic mobility and their association with mortality. (May 2023) - Ojalehto, Elsa; Finkel, Deborah; Russ, Tom C.; Karlsson, Ida K.; Ericsson, Malin
Abstract: Introduction: Both educational attainment and genetic propensity to education (PGSEdu ) have been associated with geographic mobility. Socioeconomic conditions are, in turn, associated with individuals' health. Geographic mobility could therefore lead to better health for some since it could provide better opportunities, like education. Our aim was to study how attained education and genetic predisposition for higher education are related to geographic mobility, and how they affect the association between geographic mobility and mortality. Methods: We used data from the Swedish Twin Registry (twins born 1926–1955; n = 14, 211) in logistic regression models to test if attained education and PGSEdu predicted geographic mobility. Cox regression models were then performed to test if geographic mobility, attained education, and PGSEdu were associated with mortality. Results: The results show that both attained education and PGSEdu predicted geographic mobility, in both independent and joint effect models, with higher education associated with higher mobility. Geographic mobility was associated with lower mortality in the independent effect model, but joint effect models showed that this association was completely explained by attained education. Conclusions: To conclude, both attained education and PGSEdu were associated with geographic mobility. Moreover, attained education explained the relationship between geographic mobility and mortality. Highlights: Genetic propensity to education and attained education predicted geographic mobility. Attained education explains the relation between geographic mobility and mortality. The association between education and mortality was not explained by genetic factors.